Can electro-cleaning solve the problem of membrane biofouling for membrane bioreactor? - Unal, Bahar Ozbey; Dizge, Nadir; Keskinler, Bülent; Karagündüz, Ahmet (Desalination Publ, 2021)
Membrane bioreactor (MBR) is a trustworthy and encouraging technology for wastewater treatment and reuse. However, membrane fouling limits the sustainability of this technology. Electromembrane bioreactor (E-MBR) is a promising technology for the control of membrane fouling which prevents the adhesion of the charged pollutants to the membrane surface by several mechanisms. In this study, an E-MBR system with a platinum-plated titanium anode and an activated carbon cloth membrane cathode was used for the control of membrane fouling by electro-cleaning. The effects of applied voltage (5-50 V) and direct current exposure time (1- 3-5 min) on permeate flux and, extracellular polymeric substances, soluble microbial products (SMPs) and chemical oxygen demand (COD) removal efficiencies were examined. Also, the impact of electro cleaning on reversible and irreversible membrane fouling was investigated. The maximum removal efficiencies of SMP carbohydrate, SMP protein and COD were determined as 88.1%, 86.5%, and 83.8% for 5 V and 3 min electro-cleaning time while it was about 18.8%, 80.1%, and 30.3% for without electro-cleaning, respectively. Also, the reversible membrane fouling was enhanced from 52.5% to 98.5% and the irreversible membrane fouling was decreased from 47.4% to 1.5% when the electro-cleaning was applied for 5 V and 3 min. This study showed that E-MBR provides promising results for the control of membrane fouling in MBR.
Keywords: Electro-membrane cleaning; Membrane biofouling; EPS; Domestic wastewater